\(\text{Cho ab=1.Tính }\left(a^3+b^3\right).\left(a^2+b^2\right)-ab\)

 

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

28 tháng 9 2017

\(A=\frac{1}{\left(a+b\right)^3}.\frac{a^3+b^3}{\left(ab\right)^3}+\frac{3}{\left(a+b\right)^4}.\frac{a^2+b^2}{\left(ab\right)^2}+\frac{6}{\left(a+b\right)^5}.\frac{a+b}{ab}\)

\(=\frac{1}{\left(a+b\right)^3}.\frac{a^3+b^3}{1^3}+\frac{3}{\left(a+b\right)^4}.\frac{a^2+b^2}{1^2}+\frac{6}{\left(a+b\right)^5}.\frac{a+b}{1}\)

\(=\frac{a^2-ab+b^2}{\left(a+b\right)^2}+\frac{3\left(a^2+b^2\right)}{\left(a+b\right)^4}+\frac{6}{\left(a+b\right)^4}\)\(=\frac{\left(a^3+b^3\right)\left(a+b\right)+3a^2+3b^2+6}{\left(a+b\right)^4}\)

\(=\frac{a^4+a^3b+ab^3+b^4+3a^2+3b^2+6}{a^4+4a^3b+6a^2b^2+4ab^3+b^4}\)\(=\frac{a^4+a^2.1+1.b^2+b^4+3a^2+3b^2+6}{a^4+4a^2.1+6.1^2+4b^2.1+b^4}\)

\(=\frac{a^4+4a^2+4b^2+b^4+6}{a^4+4a^2+6+4b^2+b^4}=1\)

8 tháng 9 2015

bạn có thể vào mục câu hỏi tương tự

http://olm.vn/hoi-dap/question/162856.html